Influence OF Glyceryl Guaiacol Ether On Anaesthesia In Goats - Balagopalan T P (Department of Surgery, College of Veterinary and Animal Sciences, 1986)
The present study was undertaken with the object of finding out the influence of GGE and its combinations on anaesthesia in goats. Eighteen apparently healthy cross – bred male kids, aged 5 – 9 months, weighing 11 – 16 kg were used for the study in three groups of six animals each. GGE, five per cent solution alone at the rate of 100 mg/kg was administered intravenously in group A. Triflupromazine hydrochloride at the rate of 0.2 mg/kg and GGE solution at the rate of 100 mg/kg were administered in group B. Triflupromazine hydrochloride, GGE and five per cent Thiopentone sodium solutions were administered in group C. An average of 28.00 + 0.10 ml GGE solution was administered in group A, 0.12 + 0.003 ml Triflupromazine hydrochloride followed by 24.33 + 0.67 ml GGE solution in group B and 0.12 + 0.003 ml Triflupromazine hydrochloride, 28.83 + 0.54 ml GGE and 2.97 + 0.19 ml Thiopentone sodium solutions were administered in group C. There were no untoward symptoms at the time of administration of the drugs. The induction time was 3.42 + 0.20 min. in group A, 2.08 + 0.08 min. in group B and 2.40 + 0.24 min. in group C. The induction was smooth in all the groups. On induction pedal, corneal, cutaneous and palpebral reflexes disappeared in all the groups, while palpebral reflex alone persisted in group A. Dilation of pupil with complete relaxation of jaws, anus, penis and abdomen was noticed in all the animals as the anaesthetic effect deepened. Flaccidity of tail was pronounced in group C. All the animals were found to be weak and dull and did not take feed and water upto 12 hours in group A and upto 24 hours in group B and C. They were apparently normal by 24, 36 and 60 hours in group A, B and C respectively. Reduction in rectal temperature was noted in all the groups. Initial reduction followed by an increase in heart rate was seen in group B and C. In group A there was increase in heart rate from the beginning. Tachycardia was observed at the time of recovery in all the groups. The variations in respiration rate were within the normal limits. The duration of anaesthesia was 28.83 + 2.27 min., 44.83 + 1.74 min. and 52.60 + 3.57 min. in group A, B and C respectively. The period of recovery was 18.00 + 0.89 min., 17.33 + 1.05 min. and 34.40 + 1.69 min. in group A, B and C respectively. Recovery was smooth and uneventful. There was a significant fall in the blood pressure (systolic, diastolic and mean arterial pressure) in all the groups, but pulse pressure showed marginal variation. Variations in central venous pressure was not significant. The electrocardiogram revealed a depression of S – T segment in all the groups and depression of P wave in group B and C. Tachycardia was seen at recovery. There was reduction in total erythrocyte count while the leukocyte count showed an initial decrease followed by an increase at 24 hours. The lymphocyte count decreased and the neutrophil count increased. Variation in the eosinophil and monocyte count was not significant. A reduction in the haemoglobin content and packed cell volume was observed in all the groups. The erythrocyte sedimentation was observed in all the groups. The erythrocyte sedimentation rate showed an increase during anaesthesia. Significant increase in blood glucose was noticed in all the groups during anaesthesia and the serum protein values decreased. The serum sodium values showed marginal variations but the serum potassium values showed decrease upto 120 min. There was an increase in the serum chloride values followed by a decrease in all the groups. In all the three groups of animals, variation in serum glutamic pyruvic transaminase level was within normal limits. Gross lesions were not seen in any of the animals sacrificed on 4th or 10th day. But microscopic examination, early degenerative changes were noticed in the liver and kidney of all the animals sacrificed on the 4th day. Evidence of regeneration could be observed by the 10th day.